2017
DOI: 10.4995/wrs.2017.5230
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing study of caecal bacterial community of rabbit does and kits from a farm affected by epizootic rabbit enteropathy

Abstract: Epizootic Rabbit Enteropathy (ERE) is a disease of unknown aetiology that mainly affects postweaning animals. Caecotrophs from animals in a farm affected by ERE were analysed to identify changes in the microbiological profile of growing rabbits. Does and kits at weaning (28 d) and the same rabbits ten days later (38 d) were used for a comparison using Roche 454 pyrosequencing of hypervariable V3-V5 regions of the 16S rRNA genes. The caecal bacterial community was dominated by the Firmicutes phylum (about 80%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 33 publications
8
12
1
Order By: Relevance
“…Comparison of the metataxonomic profiles showed a difference between groups ( p < 0.04), which supported the classification of this enteropathy as dysbiosis. It has been reported that ERE dysbiosis affects a rabbit’s microbiota, because it increases the abundance of the phyla Bacteroidetes, Proteobacteria, and Verrucomicrobia [ 15 , 17 ]. However, it decreases the abundance of the phylum Firmicutes [ 15 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparison of the metataxonomic profiles showed a difference between groups ( p < 0.04), which supported the classification of this enteropathy as dysbiosis. It has been reported that ERE dysbiosis affects a rabbit’s microbiota, because it increases the abundance of the phyla Bacteroidetes, Proteobacteria, and Verrucomicrobia [ 15 , 17 ]. However, it decreases the abundance of the phylum Firmicutes [ 15 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ERE dysbiosis affects a rabbit’s microbiota, because it increases the abundance of the phyla Bacteroidetes, Proteobacteria, and Verrucomicrobia [ 15 , 17 ]. However, it decreases the abundance of the phylum Firmicutes [ 15 , 17 , 18 ]. In addition, an effect on the diversity has been reported, principally on the genera Butyricimonas and Anaerotruncus [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations